Economizing and strategizing: How coalitions and transaction costs shape value creation and appropriation - Asmussen, Christian G.; Foss, Kirsten; Foss, Nicolai J.; Klein, Peter G. (Strategic Management Journal, 2021)
Abstract Research summary Research has examined how “economizing” and “strategizing” mechanisms interact in driving competitive outcomes, but the role of coalitions in this process has received little attention. Coalitions are formed to create more value (i.e., economizing) and to strengthen competitive positions (i.e., strategizing). Based on a formal coalitional model, we derive several unintuitive results. We show that economizing actions may backfire because creating more value may lead other players to strategize more aggressively, offsetting the additional value creation. Moreover, creating countervailing power—that is, building a coalition against players with significant power such as monopolists—not only allows the coalition to appropriate more value, but may also benefit the powerful trading partner by reducing competition among the coalition members. Coalition‐formation can hurt coalitions members by reducing economizing investments. Managerial summary Managers typically seek competitive advantage either by improving efficiency (by having unique resources, lowering costs, or improving managerial practices) or by trying to obtain stronger bargaining positions against their buyers or suppliers. We show that these two approaches interact in surprising ways. For example, efficiency improvements create more opportunity for profit, but also give trading partners stronger incentives to bargain for a share of that profit. At the same time, small buyers or sellers can band together into clubs or cooperatives to get better deals from a powerful trading partner, thereby restraining competition among themselves. However, large firms can try to prevent such coalitions from forming by pursuing vertical integration of potential coalition members. We explore a variety of bargaining situations and show that the ability to encourage or thwart coalition formation is an important managerial tool.